Sociality of The Baduy Community: The Progress of Baduy Community Life - Hakim, Tiyan Rahmanul; Kartini, Dede Sri; Zakaria, Saifullah (International Journal of Research in Community Services, 2025)
Baduy society belongs to the traditional society that allows it to be at the stage of a developing society. The shift in Baduy society is due to the development of the increasingly advanced times so that not only curiosity to the modern world, various new needs become one of the triggers of pikukuh baduy violations. The process of change occurs because of social relations where baduy people often interact with the outside community causing the mindset and orientation of baduy people towards the maturity of rationality of the needs of life. The phenomenon will be dissected by Emile Durkheim's theory, namely mechanical social solidarity and organic solidarity, as well as providing explanations related to indigenous pikukuh as social facts that influence the way baduy people act and think. The basis of this research is the assessment of the concepts and theories about the development of baduy society based on the search for literature contained from books and several articles that have been published. This approach was chosen to understand social phenomena or symptoms by focusing on a complete picture of the phenomenon studied.